Task-based Language Learning in Bilingual Montessori Elementary Schools: Customizing Foreign Language Learning and Promoting L2 Speaking Skills - Winnefeld, Jana (Linguistik Online, 2012)
Foreign language learning has been a part of German elementary schools for several years now. Montessori schools focusing on individual learning, i.e. mostly independent from the teacher and based on auto-education, interest, and free choice, are also asked to teach an L2. The original lack of a concept of L2 learning for this environment has brought forth different approaches. Bilingual education seems to be feasible and applicable in Montessori education. The downside to this is that even in a bilingual classroom the Montessori way of learning may not allow for very much oral production of the foreign language. The role of L2 production (cf. Swain 1985, 1995, 2005) for language acquisition has been theoretically claimed and empirically investigated. Output can have a positive influence on L2 learning (cf. e.g. Izumi 2002, Keck et al. 2006). This also applies to interaction (cf. Long 1996), where negotiation of meaning and modified output are factors supporting L2 development (cf. e.g. de la Fuente 2002, McDonough 2005). Task-based Language Learning (TBLL) presents itself as one way to promote oral language production and to provide opportunities for meaning-negotiation. Especially tasks with required information exchange and a closed outcome have been shown to be beneficial for the elicitation of negotiation of meaning and modified output. This paper argues that TBLL is a promising approach for the facilitation of L2 production and thus the development of speaking skills in a Montessori context. It also hypothesizes that TBLL can be implemented in a bilingual Montessori environment while still making the Montessori way of learning possible. Different tasks on various topics, examples of which are presented in this article, can lay the foundation for this. Offering such tasks in a bilingual Montessori elementary classroom promises to foster language production and the use of communication strategies like negotiation of meaning, both being facilitative for L2 acquisition. This hypothesis remains to be tested in future research.